Kamingaw - Pardillo, Petroska Kyana V. (Animo Repository, 2022)
In the 1970s, the Philippine government crafted the Labor Code of 1974 which institutionalized labor migration, and saw the deployment of thousands of contractual Filipino workers abroad. For the very first time during the Cory Aquino administration, overseas Filipino workers (OFWs) were hailed as bagong bayani or modern-day heroes, justifying the suffering of many Filipinos abroad under the rhetoric of sacrifice. This study aims to shed light on the complexities of the OFW phenomenon as it seeks to uncover the different facets of OFW life that enmesh themselves in making the OFW experience such a precarious one. Additionally, this study examines the ways in which relationship dynamics are affected within the Filipino transnational family.The researcher conducted a longitudinal phenomenological case study and closely followed the family of two OFWs who are currently residing in Dubai, United Arab Emirates. Through participant observation, semi-structured and unstructured interviews, the researcher was able to collect and build an understanding about the complexities of OFW life through the lived experiences of its participants. The results of this study aims to provide the audience with a deeper understanding of OFW life as it captures their experiences in a short-documentary film entitled “Kamingaw.”